CHALLENGES IN TRANSLATING LITERARY TEXTS - Hasanova Sevinch Hotam qizi (Modern American Journals, 2025)
Translating works of literature is important in ensuring that they can be read by various people regardless of language and culture. In contrast to the technical or scientific translation, translating a literary work does not only involve language accuracy but artistic and emotional values of the given work [2, p. 45]. A literary work gives a reflection on the worldview of the author, culture and his/her stylistic preferences, which are very difficult to deal with as a translator.Literary translation is a process of re-creating the image, tone of voice, rhythm and aesthetic effect with adherence to the source text. Translators usually experience a challenge in translating metaphors, idioms, wordplays and culturally specifics. These issues underline the difficulty of literary translation both as a linguistic and creative process.